2020
DOI: 10.3390/md18070342
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Roles of Diatom-Derived Oxylipins within Marine Environments and Their Potential Biotechnological Applications

Abstract: The chemical ecology of marine diatoms has been the subject of several studies in the last decades, due to the discovery of oxylipins with multiple simultaneous functions including roles in chemical defence (antipredator, allelopathic and antibacterial compounds) and/or cell-to-cell signalling. Diatoms represent a fundamental compartment of marine ecosystems because they contribute to about 45% of global primary production even if they represent only 1% of the Earth’s photosynthetic biomass. The discov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 136 publications
0
12
0
Order By: Relevance
“…359 A review of the potential biotechnological application of dinoagellate phycotoxins has been published, 360 as has a more focused assessment of dinoagellate oxylipins. 361 The use of various -omics technologies for research of diarrhetic shellsh toxins has been examined. 362 As alluded to above, the determination of absolute conguration for dinoagellate compounds, especially in "super-carbon chain" metabolites, can be extremely challenging, hence a review of methods to achieve this has been published.…”
Section: Reviewmentioning
confidence: 99%
“…359 A review of the potential biotechnological application of dinoagellate phycotoxins has been published, 360 as has a more focused assessment of dinoagellate oxylipins. 361 The use of various -omics technologies for research of diarrhetic shellsh toxins has been examined. 362 As alluded to above, the determination of absolute conguration for dinoagellate compounds, especially in "super-carbon chain" metabolites, can be extremely challenging, hence a review of methods to achieve this has been published.…”
Section: Reviewmentioning
confidence: 99%
“…For example, the anti-inflammatory effect of the lyophilized biomass of microalgae Chlamydomonas debaryana enriched with oxylipins was demonstrated on a mouse colitis model [ 258 ]. Unidentified diatom oxylipins exhibit antibacterial, anti-parasitic, anti-inflammatory, and anti-cancer properties [ 259 ]. Ethyl extracts and butanol fractions isolated from Tinospora sinensis induced an oxidative burst in macrophages by increasing the production of ROS and NO, which led to the destruction of Leishmania donovani [ 260 ].…”
Section: Therapeutic Properties Of Plant Oxylipinsmentioning
confidence: 99%
“…In particular, Miralto and co-workers [ 141 ] isolated for the first time three PUAs (i.e., 2-trans-4-cis-7-cis-decatrienal, 2-trans-4-trans-7-cis-decatrienal and 2-trans-4-trans-decadienal) from the marine diatoms Thalassiosira rotula , Skeletonema costatum and Pseudonitzschia delicatissima ( Figure 4 ). After their discovery, several other oxylipins were identified [ 158 , 159 ] with several studies on their ecological role and effects on predators (e.g., antipredator, allelopathic, antimicrobial activities) [ 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 ], along with possible biotechnological applications [ 140 , 141 ]. In particular, Miralto et al showed that 2-trans-4-cis-7-cis-decatrienal, 2-trans-4-trans-7-cis-decatrienal and 2-trans-4-trans-decadiena had anti-proliferative activity on colon carcinoma Caco-2 cells at 11–17 µg/mL and found apoptosis induction by terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) assay.…”
Section: Microalgal Bioactive Compoundsmentioning
confidence: 99%